The connotation of Chinese crab culture: a comprehensive review from the perspectives of literature, art, and diet - Yan, Xiaodie; Zhang, Cong (Frontiers in Marine Science, 2025)
Crab is a traditional Chinese culinary ingredient with significant cultural, archaeological, and artistic research value. As a prized aquatic product in China, it has become a cornerstone of the nation’s aquaculture industry. Throughout history, crab culture has evolved, developing distinct temporal characteristics and cultural connotations. However, controversies surrounding the cultural significance of crabs and the disorganization of related research materials have hindered the study and dissemination of crab culture. This paper systematically reviews and analyzes crab culture data from various historical periods, exploring cultural features in ancient literary works, artistic appreciation, and crab-eating customs. It reexamines the cultural connotation of Chinese crabs from a novel perspective encompassing literature, art, and culinary practices, aiming to enrich the temporal aspects of crab culture and promote the harmonious development of crab culture alongside the modern aquaculture industry.